PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN DAN RISK MINIMIZATION TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Ivon Nurmas Ruroh; Sri Wahjuni Latifah (Jurnal Akademi Akuntansi, 2018)
This study aims to examine the effect of profitability, leverage, size, and risk minimization to reveal corporate social responsibility for mining companies listed on the BEI for the period 2015-2016.The sample was taken by using purposive sampling that selected with the criteria that had been determined and obtained the sample of 19 companies. This study uses secondary data, namely the annual report of mining companies listed on the BEI for the period 2015-2016. This study uses multiple linear regression analysis techniques and showed that profitability variables affect to Corporate Social Responsibility, leverage effect to Corporate Social Responsibility, size effect to Corporate Social Responsibility, risk minimization affect to Corporate Social Responsibility.